Nutritional quality of some non-alcoholic beverages from the Romanian market - Busuricu, Florica; Schroder, Verginica; Margaritti , Doina; Anghel, Andreea Hortensa; Tomos, Sirma (Technium BioChemMed, 2022)
In the recent years, young consumers choose to consume from the category of soft drinks, without acknowledging that their health may be endangered. To this end, we aim to contribute to the real scientific estimation of the nutrient intake from a number of 20 waters with vitamins and minerals having a reduced addition of fruit extract (1-3%), compared to juices that have 10-30 % fruits extract, from those sold in Romania. We analyzed the presentation of the nutritional declaration, the quality of the additives and the profiling of nutrients through the SENS system. The obtained results classify the products in the category of those with low energy value and in the category “significant sources of vitamins and minerals”; there are from food classes 2 and 4, as a nutritional profile